Comparison of CSF Glucose Values Obtained by Glucometer and Autoanalyzer - Dr Alex Shibu,; Dr A. Sujatha Rani,; Dr Kotta Niranjan,; Dr Abdul Ghani Siddiqui,; Dr Purvant Shubhashri Rajendra, (International Journal of Pharma and Bio Sciences, 2024)
Bacterial meningitis is a disease with a high fatality rate and the chance of developing severe complications are more, which include hearing loss, seizures, limb weakness, and difficulties with vision, speech, language, memory, and communication. During bacterial meningitis, cerebrospinal fluid(CSF) glucose level decreases owing to increased glycolysis, impaired glucose transport, or consumption by microorganisms. The prompt estimation of CSF glucose helps decide whether to use antibiotics in patients suspected of bacterial meningitis. This study is done to determine whether a point of care device(glucometer) can be used as an alternative to estimate CSF glucose level by finding the correlation between CSF glucose values obtained by glucometer and autoanalyzer. CSF samples that are clear and not contaminated with blood received by the Biochemistry laboratory, Osmania General Hospital, during the study period were analyzed in this cross-sectional study. Glucose level is estimated in CSF samples using an amperometric glucometer. Also, the glucose level is estimated in the CSF samples by autoanalyzer via hexokinase method, which is considered as the reference method. The CSF glucose values obtained by the two methods are compared by linear regression analysis. The mean value of CSF glucose measured by autoanalyzer is 59.26 ±29.02 mg/dl, and the mean value measured by glucometer is 65.01±30.56mg/dl. The percentage bias for CSF glucose measurement by glucometer is 9.60 percent. The correlation coefficient measured by linear regression analysis is 0.9846. The standard error is 5.35mg/dl. The glucometer could not detect CSF glucose values below 20 mg/dl (measured by autoanalyzer). The glucometer indicated a low value for 28 of 32 samples with glucose values below 20mg/dl (displayed as 'low'). For the remaining four samples, glucometer showed a higher mean value with a percentage bias of 53.2 percent. Thus, a glucometer can help to detect low CSF glucose values in bacterial meningitis. The comparison of CSF glucose estimation by glucometer with autoanalyzer (reference method) gives a correlation coefficient of 0.9846. Also, the glucometer detected values below 20 mg/dl as low values (displayed as 'low'). Therefore, a glucometer can be used for point-of-care estimation of CSF glucose so that initiation of treatment with antibiotics is not delayed.